Better Blood Bank Administration Review and Bridging Epic Using QUEries (BB-BARBEQUE). (11th September 2019) - Hsu, Jim; Gowani, Faaria; Duhon, Daniel; Ipe, Tina; Leveque, Christopher; Salazar, Eric
Abstract: High-volume blood banks at academic hospitals and medical centers have increased demands for utilization review, which can be manual and laborious. Every blood bank's utilization review program is unique and depends on available personnel, staffing, and access to electronic medical records. A standardized, automated workflow for utilization review can reduce error and subjectivity and maximize efficiency. A customizable query that can accommodate different product utilization review criteria and is compatible with mainstream EMRs such as Epic is a valuable clinical tool for many practice settings. Furthermore, an efficient workflow that minimizes manual technician review and reduces provider fatigue can provide increased cost savings while maintaining compliant utilization review practices. Modern versions of Microsoft Excel, the most used data spreadsheet program worldwide, incorporate new features for data collation and analysis, namely, Power Query. Power Query enhances Excel's capabilities for self-service Business Intelligence (BI). We introduce an approach for Better Blood Bank Administration Review and Bridging Epic using QUEries (BB-BARBEQUE) and demonstrate a preliminary version of the workflow that enables ordinary end users, such as pathology residents, to conduct utilization reviews more easily and efficiently. The workflow is designed to dynamically capture product utilization data that are generated through Epic SQL reporting into a user-friendly spreadsheet format. The data are filtered by using customizable queries to capture blood product requests that are most likely to yield actionable results. Our reviews included blood product requests for units of packed red blood cells, platelets, fresh-frozen plasma, and cryoprecipitate, as well as extensive associated metadata, including the ordering unit, patient identifiers, provider names, dates and times of product use and laboratory collection, and most recent laboratory values for hemoglobin, platelet count, INR, and fibrinogen. We compare this approach to the previous, manual workflow. Incidences deemed inappropriate for product use are tracked and compared with both approaches, through a metric designed to evaluate the number of successful provider contacts, either through a form letter or telephone call. We also provide preliminary comparisons of technician time saved by adopting this procedure compared to the previous approach. Overall, we show that automation of key steps in the utilization review procedure can significantly increase efficiency while improving the end-user experience, and we demonstrate an end-user product that is translatable to many institutions using an Epic EMR backend.